You are on page 1of 1

# 4

Chapter 1. Introduction
with initial values greater than 2 diverge from y (t) = 2. For 0 < y < 2, the slopes are also positive, and hence solutions with initial values between 0 and 2 all increase Chapter 1. Introduction (The missing solutions others). toward the solution y (t) are = 2. similar For y < to 0, the slopes are all negative; thus solutions with initial values less than 0 diverge from the solution y (t) = 0. 15. -(j ) y = 2 y .

16

1.3 16 1.3 16
16

Chapter 1. Introduction

erential equation is second order, since the highest derivative in the 1. The 16. -(c) di y = y 2. equation is of order two. The equation is linear, since the left hand side is a linear function and derivatives. 17. -(g ) of y y= 2 its y . Chapter 1. Introduction

1.3

1. The order, since since the the highest highest derivative derivative of in the the erential equation is second 3. fourth order, 18. -(b) di y = 2 + y. equation y isis ofof order two. The equation is is linear, since the leftthe hand sidecontaining is a linear function order four. The equation also linear, since terms function and its the dependent variable is linear in y and its derivatives. 19. -( h) of y y= y (3 derivatives. y ).

Chapter 1. Introduction

1.3

The di erential equation isfourth second order, since the highestderivative derivative in the 3.1. The di erential equation order, the highest of the 4. The equation is is rst order, since since the only derivative is of order one. 20. -( e) di yerential = y (y 3). equation is of order two. The equation is linear, since the left hand side is a linear function y is of order four. The equation is also linear, since the terms containing The dependent variable is squared, hence the equation is nonlinear. function of y and its derivatives. the dependent variable is linear in y and its derivatives. 23. The dierence between the temperature of the object and the ambient temper5. The ature is dierential equation is second order. Furthermore, the equation is nonlinear, The di erential equation is an fourth order, since the highest derivative of the 4.3. The didependent erential equation is order, since the only derivative is of order one. 1. The is second order, since the highest derivative innot the since the variable y rst is argument of the sine function, which is a u 70 , uthe in F. linear, function y is of order four. The equation is also since the terms containing The dependent variable is squared, hence equation is nonlinear. equation is of order two. The equation is linear, since the left hand side is a linear linear function. the dependent variable is linear in y and its derivatives. function y and derivatives. Since theof object isits cooling when u> 70, and the rate constant is k = 0.05 min1 , t is second t order. Furthermore, 5. The di erential equation the equation 7. y ( t ) = e y ( t ) = y ( t ) = e . Hence y1 y1 = Also, y2 ( t) is =nonlinear, cosh t 1 1 1 the governing dierential equation for the temperature of0. the object is 4. The di erential equation is rst order, since the only derivative is of order one. since the dependent variable y is an argument of the sine function, which is a 3. dierential is fourth order, since the highest derivative of not the y1 (The t) = sinh t and yequation t. Thus y2 y 2 (t) = cosh 2 = 0. The dependent variable is squared, hence the equation is nonlinear. linear function. du function y is of order four. The equation is also linear, since the terms containing = .05 (u 70). the variable linear in y its derivatives. 9. dependent y (t) = 3t + t2 y is (t) =3+ 2t . and Substituting into the dierential equation, we dt t t 2 di equation second order. equation is cosh nonlinear, 7.5. The yt1 (t) = e yt t)t2 = (is t)+ = .Hence y . y1 = 0. the Also, y2 (tfunction )= t have (3 + 2erential t ) (3 + )y = 2e t2 3t t2 Furthermore, = Hence the given is a 1( 13 1 t variable y is an argument since the dependent of the sine function, which is not y ( t ) = sinh t and y ( t ) = cosh t . Thus y y = 0. 4. dierential isamount rst order, since the only derivative in is of order one. a solution. 1TheLet 2 2 drug 2 24.(a) M (t) beequation the total of the (in milligrams) the patients linear function. The dependent variable is squared, hence equation is nonlinear. body at any given time t (hr). The drug is the administered into the body at a constant 2 (t) = 3 + 2t. Substituting into the 9. y ( t ) 3= t+ y1 di equation, we 10. of y (t)mg/hr. t/t3 y (rate t) = at 1/3 and the y1 (drug t) = y y1 (t )erential = 0. Clearly, y1 ( t) 1= 1 (t) = rate 500 The which leaves the bloodstream is given by t 2 t 2 2 y2 y = t t t 7. y ( t ) = e y ( t ) = y ( t ) = e . Hence 0. Also, y ( t ) = cosh have t (3 + 2 t ) (3 t + t ) = 3 t + 2 t 3 t t = t . Hence the given function is 1 1 2 5. di erential equation is order. the + equation is nonlinear, is a (solution. Likewise, y (second t) = e + t/ 3Furthermore, y2 = e 1by /3, the y (t )erential = e ta , 1 1(t) 21 2di 0 .4The M t ). Hence the accumulation rate of the drug is described t t y ( t ) = sinh t and y ( t ) = cosh t . Thus y y = 0. solution. since is an argument ofthe theleft sine function, which is not a y2 1(tthe ) = dependent e , y2 (variable t)2= e .y Substituting into hand side of the equation, 2 2 equation linear function. we nd that et + 4(et ) + 3(et + t/3) = et 4et + 3et + t = t. Hence both dM 2 (t into the dierential equation, we 9. y ( t ) = 3 t + t y ) = 33 + 2t.Substituting 10. y ( t ) = t/ 3 y ( t ) = 1di / and y ( t ) =(mg/hr) y1 (t) =. y1 (t) = 0. Clearly, y1 (t) = 500 0 .4 M functions erential equation. 1 are solutions1 of the 1 dt 2 2 2 2 t t the given tis a t y t) Likewise, (3 ) = 3 t + 2 t 3 t t = . Hence ishave a y( ( t ) = e + t/ 3 ( t ) = e + 1/y 3, y= (cosh t) = e , 7. y1solution. (tt )(3 =+ et2 y1 (tt )+ = ty1 t ) = e . Hence y y = 0. Also, t 2 2 (t) 2 function 1 2 1 t t solution. 1 /y 2 y 1t / 2 Thus y 3/2hand side of the equation, y ( t ) = e , ( t ) = e . Substituting into the left y11. ( t ) = sinh t and ( t ) = cosh . y = 0. y1 (t) = t 2 /2 and 2y1 (t) /4. Substituting into the 12 2 y1 (t) = t 2 = t t (b) we nd that e + 4( et ) + 3( ethave + t/3) = et 4et + 3et + t = t. Hence both left hand side of the equation, we 10. y13 (t ) = t/ 3 y tthe )3 =+ 1/ 3 y1 (t) = y =y (t) = 0. equation, Clearly, we y1 (t) functions are solutions di equation. 9. y (t) = + t2 y ( tof )(= 2 terential . and Substituting into the di 1 1 (t) 1 erential t t1/2 t 2e 2 2 3/ 2 t2 ) = 3 1/ 1 / 2= 1 / 2 1 / 2 is a solution. Likewise, y ( t ) = + t/ 3 y ( t ) = e + 1 / 3, y ( t ) = e 2 have t(3 + 2t2 )( (3 t + t + 2 t 3 t t t . Hence the given function is a , 2 t /4 + t (t /2 ) t = t /2 + 3 t /2 t 2 t/2 1 1 / 2 3 / 2 y2 (y t) = e , y ( t ) = e . Substituting into the left hand side of the equation, 11. ( t ) = t y ( t ) = t / 2 and y ( t ) = t / 4. Substituting into the solution. 1 2 1 1 =0 t t wehand nd that + 4( et ) + 3( e + t/3) = et 4et + 3et + t = t. Hence both left sideeof the equation, we have are solutions of the dierential equation. 10.functions y1 (t) = t/3 y y 1 1 (t) = 1/3 and 2y1 (t) = y1 (t) = 31 (t) = 0. Clearly, y1 (t) Likewise, y2 ( t3 y/ t2 . Substituting into left =2 t 2t) = /2 y2 (t) = 1/t 2 t and 1 2(t) 1/ 2 1 /2 the 2 is a solution. Likewise, y ( t ) = e + t/ 3 y ( t ) = e +t1 1/ / 3, y2 ( t) = et , 2t (t /4 ) + /2 ) t = /2 + 3 /2 t 2 3t(t 2 t 1 / 2 erential t equation, 1/2 3/2 hand side of the di we have t t) = t2 (t y1e (t) .=Substituting t /2 and into y1 (tthe ) = t hand /4.side Substituting into the 1( y2 11. (t) =y e ,y )= of the equation, = 0 left t of the t we t t t t side equation, have weleft ndhand that e + 4( e ) + 3( e + t/ 3) = e 4 e + 3 e + t = t . Hence both 2 1 2t2 (2 t3of )+ 3t( t ) tequation. = 4 t1 3 t1 t1 = 0 . functions are solutions the di erential Likewise, y2 (t2 ) = t1 y (t) = t2 and y2 t3 . Substituting into the left /( 2t) = 2 1 2t (t3/2 /4 )2+ 3t(t1/2 /2 ) t1 = t /2 /2 + 3 t1/2 /2 t1/2 hand side of the dierential equation, the we have are solutions 3/2 Hence both di erential 11. y1 ( t) = functions t1/2 y1 (t) = t1/2 /2 of and y1 ( t) = /4. Substituting into the = 0t equation. left hand side of the equation, we have 3 2 2 t2 (2 t 1 = 4 t1 )= +3 t( t3 ) y t t1 t1 =into 0 . the left hand 12. y1 (t) = t2 y t) and 6 t4 .3 Substituting 1( 1 2t 2 1 (t) = 3 Likewise, y ( t ) = t y ( t ) = t and y ( t ) = 2 t . Substituting into the left 2 2 2 2 1/ 2 have 1/2 side of the di erential equation, we 2t2 ( t3/di / 4erential ) + 3t(t /2 ) we t have = t1/2 /2 + 3 t1/2 /2 t1/2 hand both side of the equation, Hence functions are solutions of the di erential equation. =0 4 2 t2 (6 t )+ 5 t(2t3 ) + 4 t2 = 6 t2 + 4 t 2 = 0 . 2 3 2 1 1 10 t 1 t 3 t (2 + 32 tt ( t and ) t (t) = 3 t t 1 = 0 . the left hand 12. y1 (t) = t2 2 y1 (t) ) = y1 =4 6t t4 .Substituting into Likewise, y2 ( t)= t1 equation, y2 (t) = we t2have and y2 (t) = 2 t3 . Substituting into the left side of the di erential hand sideboth of the dierential wethe have Hence functions are equation, solutions of dierential equation. 2 4 3 2 t (6 t ) + 5t(2t ) + 4 t = 6 t2 10 t2 + 4 t2 = 0 . 22 3 23 1 1 4 1 12. y1 (t) =2 tt t) 3 = 2 t and (t4 )t = 6 t 3. (2 ty )(+ t(t ) ty = t Substituting t1 = 0 .into the left hand 1 1 side of the dierential equation, we have Hence both functions are solutions of the dierential equation. t2 (6 t4 ) + 5t(2t3 ) + 4 t2 = 6 t2 10 t2 + 4 t2 = 0 . 12. y1 (t) = t2 y1 (t) = 2t3 and y1 (t) = 6 t4 . Substituting into the left hand